Rola języka angielskiego jako języka pośredniczącego i docelowego w kontaktach międzykulturowych i międzyetnicznych - Wiśniewska, Katarzyna (My University, 2015)
Analiza komunikacji międzyludzkiej stanowi znakomitą część współczesnego językoznawstwa, jako że wiąże się ona z wieloma procesami, mechanizmami i siłami operującymi w globalnej przestrzeni komunikacyjnej, które wywierają presję na języki naturalne, społeczności etniczne i kulturowe, jak również pojedynczych komunikatorów podczas różnorakich aktów komunikacji. Celem pracy jest podjęcie analizy wybranych języków naturalnych wchodzących w kontakt z innymi językami naturalnymi w charakterystycznych warunkach kontaktu językowego. Praca ma na celu analizę wyników badania przeprowadzonego w dwóch przypadkach kontaktu językowego, to jest w kontakcie językowym występującym w triadzie: język arabski-język angielski-język polski oraz w diadzie: język polski-język angielski. Głównym celem analizy badanych kontaktów językowych jest ustalenie statusu jaki osiągają języki na globalnej arenie języków naturalnych, jak również wśród rodzimych komunikatorów/społeczności komunikacyjnych. Analiza roli języka angielskiego jako pośredniczącego dotyczy kontaktu językowego w triadzie: język arabski-język angielski-język polski, natomiast rola języka angielskiego jako docelowego badana jest w warunkach kontaktu językowego rozumianego jako diada: język polski-język angielski.

The analysis of human communication constitutes a substantial part of modern linguistics since it involves a number of interplays of processes, mechanisms and forces which have an effect on one another and reach natural languages, ethnic communities, cultures and environments of communicators within the global communication space. The objective of the dissertation is to undertake an analysis of selected natural languages coming into contact within the global communication space under specific conditions of language contact. With the above objective in mind, research has been conducted on a case of language contact in the triad: Arabic-English-Polish as well as in the dyad: Polish-English. The aim of the present thesis is to undertake an analysis of the circumstances of the language contact in the triadic and dyadic arrangements in order to make an attempt at determining the position of the natural languages in the natural language global arena as well as the status the languages achieve within the native speech communities. The analysis of the role of English as a mediating language is undertaken during research on language contact in the triad: Arabic-English-Polish, whereas the dyadic arrangement of language contact between Polish and English provides data on the role of English as a target language.
The role of English as a mediating and target language in intercultural and interethnic contacts
Wydział Neofilologii
Keywords: Języki naturalne; Natural languages; Kontakt językowy; Language contact; Transkomunikacja; Transcommunication; Interkomunikacja; Intercommunication